(untitled) (European Bison Conservation Newsletter, 2011)
The last bison were eliminated through hunting in Western Ukraine in early 18th century. Numerous attempts to reacclimatize the species in the beginning of 20th century were not successful. In the second part of the 20th century, during the period between 1965–1980, these animals were brought into five areas in the west of the country, thus, creating the following six populations: three in mountains – and three lowland. In the 1990s, bison numbers reached their peak i.e. 470 to 480 individuals. It the early 21-st century, a decrease of this population was recorded, due to poaching, diseases, forage shortage, and some other reasons. As of 2011, the total number of this species amounts to about 80 individuals. Two sub-populations (Klevan and Nadvirna) ceased to exist while Bukovyna and Tsuman are endangered.